2020
DOI: 10.1152/japplphysiol.00239.2019
|View full text |Cite
|
Sign up to set email alerts
|

Chronic effects of muscle and nerve-directed stretching on tissue mechanics

Abstract: Tissue-directed stretching interventions can preferentially load muscular or non-muscular structures such as peripheral nerves. How these tissues adapt mechanically to long-term stretching is poorly understood. This randomized, single-blind, controlled study used ultrasonography and dynamometry to compare the effects of 12-week nerve-directed and muscle-directed stretching programs versus control on: maximal ankle dorsiflexion range of motion (ROM) and passive torque, shear wave velocity (SWV; an index of stif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 62 publications
1
62
1
1
Order By: Relevance
“…Thus, we suggested that stretching intensity was important to decrease muscle stiffness than stretching duration. Recently, the previous studies indicated that the dorsiflexion ROM could be increased immediately and chronically increased after stretching intervention because of the change in sciatic nerve stiffness not muscle stiffness (Andrade et al, 2018(Andrade et al, , 2020. However, in this study, the change in sciatic nerve stiffness was not measured.…”
Section: Discussionmentioning
confidence: 71%
“…Thus, we suggested that stretching intensity was important to decrease muscle stiffness than stretching duration. Recently, the previous studies indicated that the dorsiflexion ROM could be increased immediately and chronically increased after stretching intervention because of the change in sciatic nerve stiffness not muscle stiffness (Andrade et al, 2018(Andrade et al, , 2020. However, in this study, the change in sciatic nerve stiffness was not measured.…”
Section: Discussionmentioning
confidence: 71%
“…The discrepancy can be attributable to different training modality, such as intensity, frequency, number of exercises, and overall duration (Freitas et al 2018 ). Concerning GM muscle stiffness, another possible explanation could be that PST affected differently the stiffness of the individual triceps surae muscles and/or the regional stiffness within each muscle, as observed by shear-wave ultrasound imaging technique (Andrade et al 2020 ). Nonetheless, it seems that combining several weeks of training with high weekly exercise frequency, as it has been done in the present study, can lead to MTC and GM muscle stiffness adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…Since previous studies showed that the different triceps surae muscles can undergo different strain during stretch exercise (Hirata et al 2016 ) and within the same muscle different portions can be unequally affected by the stretch manoeuvre (Andrade et al 2020 ), we examined the possible PST-induced architectural adaptations in all triceps surae heads at different regions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations